Roles of intestinal glutamate dehydrogenase and glutamine synthetase in environmental ammonia detoxification in the euryhaline four-eyed sleeper, Bostrychus sinensis - Peh, W.Y.X. (2014)
10.1016/j.aquatox.2010.01.018